Empowering PCIM China through the establishment of a productive social business to promote the Risalah Islam Berkemajuan in the international world - Muhammad Hamdi; Rintan Nuzul Ainy; Farid Maruf (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2023)
Muhammadiyah is an amar ma'ruf nahi munkar movement that has proved capable of transcending time for more than a century. During this time, Muhammadiyah has demonstrated its ability to serve the Indonesian people via humanitarian endeavors in the sectors of da'wah, education, and health. Along with the organization's growth, Muhammadiyah began to pioneer and extend its worldwide presence in 2000. PCIM China is one of the PCIMs that are currently being developed. Initiated in 2016 and subsequently formally created in 2016, PCIM China was able to gather together Indonesian students studying in China who had ideological and biological links to Muhammadiyah. However, when the COVID-19 epidemic struck, PCIM China was confronted with a number of issues that required treatment. First, due to the pandemic, all PCIM China administrators had to return to their homeland. Second, the number of cadres is limited. Students and students who join PCIM China do not only consist of cadres who really understand the organization, but also students who have never been involved in active management at Muhammadiyah. Third, there is no business charity that can be used as the main activity of PCIM China. The purposeful solution is the establishment of a productive social business in the form of activities that facilitate religious education and religious tourism activities in China in collaboration with the China Islamic Association (CIA). Since 2019, there has been good communication, including discussing the progress of Islam in China and the CIA's success in building mosques throughout China and madrasahs, or Islamic schools, in Beijing City. The implementation method that will be used is consult-training, Implementation of the solution is carried out by providing assistance, starting from planning the establishment of a productive business charity up to the operational stage. Apart from that, training will also be carried out for prospective business charity managers so that later they can manage productive business charities well.